2019
DOI: 10.1016/j.scriptamat.2019.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Observation of internal oxidation in a 20% cold-worked Fe-17Cr-12Ni stainless steel through high-resolution characterization

Abstract: It is often assumed that internal oxidation cannot occur at temperatures below 400ºC. However, in the present work, internal oxidation was observed in a 20% cold-worked Fe-17Cr-12Ni stainless steel (SS) after exposure to simulated primary water of a pressurized water reactor at 340ºC and not in a similarly tested sample without prior cold-work. The formation of discrete Cr-oxide precipitates and the role of cold-work are discussed. The internal oxidation model is also proposed as a plausible stress corrosion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 33 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…Due to the increased resolution, discrete oxide precipitates and Ni segregation surrounding these precipitates are observed under the Cr-Fe spinel oxide layer. The formation of the discrete Cr-rich oxide precipitates has been proven to be due to low-temperature internal oxidation [55]. Similar results about the Ni segregation have also been reported by Shen et al [56] in the study of 316 stainless steel exposed to PWR primary water at 340 ºC via TEM and by Kruska et al [63] in the study of 304 stainless steel exposed to PWR primary water at 360 ºC via APT.…”
Section: Fe-16cr-11ni Alloysupporting
confidence: 78%
See 2 more Smart Citations
“…Due to the increased resolution, discrete oxide precipitates and Ni segregation surrounding these precipitates are observed under the Cr-Fe spinel oxide layer. The formation of the discrete Cr-rich oxide precipitates has been proven to be due to low-temperature internal oxidation [55]. Similar results about the Ni segregation have also been reported by Shen et al [56] in the study of 316 stainless steel exposed to PWR primary water at 340 ºC via TEM and by Kruska et al [63] in the study of 304 stainless steel exposed to PWR primary water at 360 ºC via APT.…”
Section: Fe-16cr-11ni Alloysupporting
confidence: 78%
“…The magnified image shows that the crack flanks have also been oxidized. The oxides on the crack flanks are mainly composed of Cr and Fe, which has been reported to be Cr-Fe spinel [55,56]. Ni is nearly exhausted in the oxides and is believed to be expelled to the surrounding regions.…”
Section: Fe-16cr-11ni Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Wang et al 40 experimental results show that the CW-induced deformation can enhance the general corrosion of 304 SS in simulated PWR primary water. Shen et al 41 observed selective and internal oxidation in a 20% cold-worked 316 SS after exposure to simulated PWR primary water at 340°C. Some studies have investigated the effects of hydrogen or CW on localized corrosion and SCC of alloy materials.…”
mentioning
confidence: 99%
“…Some studies have investigated the effects of hydrogen or CW on localized corrosion and SCC of alloy materials. [31][32][33][34][35][36][37][38][39][40][41][42][43] However, it is necessary to investigate the combined effects of hydrogen in the alloy and prior CW on the metallic corrosion behavior in hightemperature water, with important implications to our understanding of SCC. In particular, the region surrounding active crack tips in PWRs is expected to experience local deformation and higher levels of H then their surroundings.…”
mentioning
confidence: 99%